PENGEMBANGAN MEDIA ANIMAL FLASH CARD SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN KOSA KATA DAN PEMAHAMAN BAHASA ANAK USIA DINI DI RA ANNURIYAH BELIKANGET - Agus Fathoni Prasetyo; Umi Rosidah (Alzam: Journal of Islamic Early Childhood Education, 2023)
The animal flash cards used at RA Annuriyah Belikanget are cards with pictures of animals with the name of the animal written underneath. Meanwhile, what the researchers developed were cards with pictures of animals using 3 languages, namely Indonesian, Javanese and English. The aim of this development is to introduce and enrich language in early childhood. This research provides answers to the problem formulation (1) What is the validity of Animal flash card media in improving language skills and vocabulary understanding of early childhood at RA Annuriyah Belikanget? (2) How effective is Animal flash card media in improving language skills and vocabulary understanding in early childhood at RA Annuriyah Belikanget? (3) How practical is Animal flash card media? The type of research used is research and development using the 4-D development model. From the research results it can be concluded that: (1) Based on validity test data, animal flash card media in language material meets the category of very valid or very feasible. (2) Based on the level of practicality, the animal flash card media developed obtained a percentage of 93.3% from the teachers' response to the media developed. (3) Based on effectiveness, animal flash card media from data acquisition and data analysis of the effectiveness of animal flash card media product development shows a high increase according to the gain score calculation resulting in the final activity value being higher than the initial activity value.